SUB-LETHAL TITANIUM DIOXIDE NANOPARTICLES (TiO2 NPs) INDUCES DISRUPTION OF CHLOROPHYLLS AND SELECTED ANTIOXIDANTS ACTIVITIES ON CHLOROIDIUM ELLIPSOIDEUM (GERNECK) - Matouke M. Moise (Polish Journal of Natural Sciences, 2023)
The increasing production of manufactured product containing TiO2 NPs is a global threat that raises concern for freshwater biodiversity and human health. The objective of this study was to examine the chronic effects of TiO2 NPs on the biomass (chlorophyll a, b) and antioxidant activities (catalase (CAT), superoxide dismutase (SOD), glutathione reductase (GRx) and malondialdehyde (MDA) of C. ellipsoideum exposed to sublethal doses of TiO2 NPs. The initial, exposure of C. ellipsoideum to acute doses of TiO2 NPs demonstrated toxicological response with EC50 69.90 mg L-1. However, the effects of sub-lethal concentrations on the microalgae showed significant reduction (p < 0.05) of Chlorophyll a and b with the increase of sub-lethal concentrations of TiO2 NPs. The percentages of increment on selected markers of oxidative stress in this study increased compared to the control; Catalase (18.30–58.66%), SOD (2.68–16.85%), GRx (26.50–86.67%) and MDA (40.00–106.00%). This study suggests that sub-lethal exogenous concentrations are disruptive to the physiology of C. ellipsoideum. Therefore, care should be taken when handling and disposing of manufactured products containing TiO2 NPs. This study is useful for understanding the potential harmful effects of TiO2 NPs bioaccumulated in aquatic ecosystems. Further studies are recommended on other commonly used nanomaterials and their physiological influence on microalgae.